International economics - Grubel, Herbert G. (Homewood, Ill. : R.D. Irwin, 1981)
This book has been structured for a two-semester course in which the sequence of real and monetary aspects is not important
Includes index.
Bibliography: p. 691-709.
ijb, 14/01/2019
Loans
Keywords: International trade; International economic relations; International finance